Post-COVID-19 strategies for higher education institutions in dealing with unknown and uncertainties - Rasli, Amran; Tee, Mcxin; Lai, Yin Ling; Tiu, Zian Cheak; Soon, Eu Hui (Frontiers in Education, 2022)
The COVID-19 global pandemic outbreak has presented higher education institutions with the impediment of transforming to a new curriculum, pedagogy, and educational management. Inevitable transformation in higher education triggered by COVID-19 is still ongoing, albeit most countries are now at the endemic stage. However, transformation should not just be about simply changing instructional delivery. The COVID-19 pandemic is a unique opportunity for educators and policymakers to rethink education systems and reimagine what is important, necessary, and desirable for future generations. Hence, this study focuses on identifying strategies for higher education institutions to deal with unknown uncertainties during and after the pandemic. Expert Opinion Method was conducted involving five professors who are senior management in their respective universities and have been directly involved in formulating strategies and policies during the pandemic. Four major dimensions were developed from the findings: (1) Resilience and Change Management, (2) Digital Transformation and Online Learning, (3) Curriculum Change, and (4) Sustainability. Flexibility is also the most common issue discussed by experts. Based on thematic analysis, post COVID-19 strategic framework for higher education institution sustainability is proposed. In addition, this study can be a roadmap for educators, policymakers, and all relevant stakeholders to prepare for future disruptions in the education sector.